Assessment of Stress in Dogs Under Cancer Therapy via Faecal Cortisol Metabolite Analysis: A Pilot Study - Christina Ziegerhofer; Alexander Tichy; Miriam Kleiter; Birgitt Wolfesberger; Rupert Palme (Animals)
Stress reactions play an important role in animals’ ability to cope with various situations. Glucocorticoids are measured as a stress parameter, and analysis of their faecal metabolites has proven to be a good method for evaluating long term stress. We hypothesised that dogs suffering from cancer would have a higher stress level during cancer therapy, which would be reflected in higher levels of faecal cortisol metabolites (FCMs). Faeces were collected from 40 dogs receiving radiation or chemotherapy before and during the treatment, and from 53 healthy dogs, who served as a control group. FCMs were extracted and quantified by a cortisol enzyme immunoassay. The results showed that the stress levels were not significantly higher in the cancer patients before therapy compared to those in the control group. Additionally, there were no significant differences in the FCM concentrations of dogs at specific time points during chemotherapy or radiotherapy. Therefore, suspected stress should not be a criterion to exclude animals from cancer treatment. Such a treatment seems ethically justifiable if it is expected to provide benefits and improvement in the quality of life for patients.